PENGEMBANGAN LKS BERBASIS PENDEKATAN REALISTIC MATHEMATICS EDUCATION UNTUK MENINGKATKAN KEMAMPUAN MATEMATIS SISWA - tri andari; Eva Komsiatun (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2018)
This research aims to develop worksheets students (worksheets) based on this Mathematics Education (RME) to improve the matematical ability of elementary school student. The subject of this research is the students of class V Elementary School of Muneng and students in grade 5 Elementary School of Pulerejo 3. The type of this research is the Research and Development, with development model Four-D (4D), which is divided into 4 stages, namely : stage defining (define), stage design (design), development stage (· develop), spreading stage (disseminate). This research done only until the development phase (develop). The products of this research is a Worksheet Students (worksheets) based on this Mathematics Education (RME) a syllabus, denunciating, worksheets, and THB through Fax Banking. The results of the study showed that the average validity is 82,689% stated valid, the results of the average convenience of a limited test is 88,75% and field tests is 80.7% stated practical, and the results of the average effectiveness of limited test is 89,33% and field tests 86% is declared effective. Based on the results of research that the students work sheet (worksheets) based on this Mathematics Education (RME) on the matter arose space stated valid, practical, and effective and improve the matematical ability of elementary school student so that it can be used in the mathematics teaching.